A moral cient??fica como supera????o da moral tradicional na filosofia da educa????o em An??sio Teixeira - Silva, Jo??o Batista da (2017)
This dissertation focuses on scientific morality as a means of overcoming traditional morality featured on the work ???A brief introduction to philosophy of education: the progressive school or the transformation of school??? by An??sio Teixeira. The philosophical view presented in Teixeira???s work was heavily influenced by two works of John Dewey: Experience and education and Democracy and education: introduction to the philosophy of education. Based on these two references, more directly on the first one, in which Dewey developed the theory of experience, Teixeira approached the issue of traditional versus scientific morality. Teixeira???s claims that the traditional morality, which prevailed in his context and that had in the catholic church its most vocal supporters, did not assure that the school, as a medium of education, could cater to a society that had been undergoing fast transformations. This morality, Teixeira argued, harbored in its entirety rigid and authoritarian principles that did not contribute for an optimal individual development once blind obedience, inaction, the respect to books, and professors were unquestionable rules. Therefore, in a society in which, due to scientific progress, had been going through continuous changes in its social tapestry and, above all, with a visible democratic tendency, called for schools to adopt in its pedagogical practice the scientific morality that embraced the advances stemming from the experimental morality. Teixeira argument on the relevance of scientific lied on the fact that it would contribute for a democratic education due to the sheer fact that it would grant the individual freedom of expression of his personality. It would also allow the individual to make his own choices and bear its inherent responsibilities in a way permitted him to be capable of self-government becoming his own master and a promoter of social welfare.